THE EFFECT OF ELECTRONIC WORD OF MOUTH AND SOCIAL MEDIA MARKETING ON THE PURCHASE DECISION OF BILLIONAIRE'S PROJECT PRODUCTS THROUGH PRODUCT QUALITY - Suharyanto Suharyanto; Nial Riyadi Rahman (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study was to analyze the effect of Electronic Word of Mouth and Social Media Marketing on the Purchase Decision of Billionaire's Project clothing with Product Quality as the Mediation variable. The research design used is quantitative research with associative methods, namely methods that are formulated to provide answers to problems that have a relationship or influence between 2 or more variables. The data used is primary data obtained through distributing questionnaires to 105 respondents with the criteria that they are buyers of Billionaire's Project products. The results of the study indicate that the Social Media Marketing variable has a direct or indirect effect on purchasing decisions. Meanwhile, the Electronic Word of Mouth variable has no direct effect on the Purchase Decision. However, through the Product Quality variable as a mediating variable, Electronic Word of Mouth has an effect on Purchase Decision.